Distribution and development of disease oats (hulled and holozernoho) in the forestrysteppes of Ukraine - Retman, S.V.; Panchenko, Y.S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of monitoring the development and spread of disease in oats forestrysteppes of Ukraine in the early stages of organogenesis.